Aptamers Selected by Cell-SELEX for Theranostics - Fang, Xiaohong; Tan, Weihong (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This edited volume describes cell-SELEX as the fundamental tool used to generate aptamer molecules for a wide range of applications in molecular medicine, bioanalysis and chemical biology. Easily integrated into the natural heterogeneous cell matrix, aptamers can be effectively used in theranostics, bioanalysis, environment detection and biomedical studies. The book gathers reviews that reflect the latest advances in the field of aptamers, and consists in fourteen chapters demonstrating essential examples of these aptamers and aptamer-nanomaterial assemblies, depending on the types of applications and biological systems. It also includes a separate chapter on the utilization of aptamers in real clinics and what will be required to achieve this significant goal. The book will be both appealing and useful to a broad audience, including biologists, bioscientists, and clinicians whose interests range from chemistry and biomedical engineering to cell and molecular biology and biotechnology. Weihong Tan is a Distinguished Professor of Chemistry and Biomedical Engineering at Hunan University, China and also a University of Florida Distinguished Professor and V.T. and Louis Jackson Professor of Chemistry at the University of Florida, USA. Xiaohong Fang is a Professor at the Institute of Chemistry, Chinese Academy of Sciences, China.
From the Contents: Introduction to Aptamer and Cell-SELEX -- Cell-SELEX Based Selection of Aptamer for Cancer Cells -- Cell-SELEX Based Selection of Aptamer for Other Intact Systems.
Description based on publisher-supplied MARC data.
Keywords: Biotechnology; Cancer research; Molecular biology; Nucleic acids; Biotechnology; Cancer Research; Molecular Medicine; Nucleic Acid Chemistry